An experimental method to estimate the mass transfer through the interfacial region of liquid membrane systems - Cárdenas, Antonio; Fillous, Lauriane; Rouviere, Jacques; Salager, Jean Louis (Ciencia)
A simple and reliable experimental method is reported to measure the mass transfer resistance through a liquid membrane as found in multiple emulsions for drug controlled release. A straightforward data analysis leads to calculate the mass transfer coefficient corresponding to the crossing of the interfacial region. The method is used to discuss some typical results with both oil and water soluble tracers.